2012
DOI: 10.1101/cshperspect.a011544
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Eukaryotic Translation Initiation: New Insights and Challenges

Abstract: Translation initiation in eukaryotes is a highly regulated and complex stage of gene expression. It requires the action of at least 12 initiation factors, many of which are known to be the targets of regulatory pathways. Here we review our current understanding of the molecular mechanics of eukaryotic translation initiation, focusing on recent breakthroughs from in vitro and in vivo studies. We also identify important unanswered questions that will require new ideas and techniques to solve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
472
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 450 publications
(482 citation statements)
references
References 133 publications
(222 reference statements)
6
472
0
4
Order By: Relevance
“…To obtain a fuller appreciation of where eIF4F fits into the grand scheme of things, the reader may find one or more of the closing references to reviews useful (72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85) …”
Section: Other Complicationsmentioning
confidence: 99%
“…To obtain a fuller appreciation of where eIF4F fits into the grand scheme of things, the reader may find one or more of the closing references to reviews useful (72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85) …”
Section: Other Complicationsmentioning
confidence: 99%
“…Located within transcript leaders of protein coding genes, uORFs are cis-regulatory elements that affect translation of the downstream main ORF (Somers et al 2013;Wethmar 2014;Hinnebusch et al 2016). uORF regulatory effects can be conceptualized through the scanning model of translation initiation, in which the preinitiation complex binds the 5 ′ end of transcript leaders and scans downstream in search of start codons (Hinnebusch and Lorsch 2012). If initiation occurs at a uORF, there are two possible outcomes: The uORF can act as a repressor of translation of the main ORF, potentially triggering mRNA turnover through nonsense-mediated decay; alternatively, uORFs can act as stress-specific enhancers by promoting downstream reinitiation at main ORFs.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…60 eIF1 (12.7 kDa) and eIF1A (16.5 kDa) are 2 proteins that work in tandem to ensure correct start codon recognition. 27,61 eIF1 suppresses initiation from non-cognate codons or start codons in improper context. 61 Directed hydroxyl radical probing and X-ray analyses (»7.9-9.0 A ) involving mammalian 40S and eIF1 showed that eIF1 binds to helices 44, 24 and 45 of the 18S rRNA near the P-site.…”
Section: E999576-6mentioning
confidence: 99%
“…Poly(A)-binding protein (PABP) is believed to enforce a "closed loop" mRNA conformation via interaction with eIF4G. Following recognition of the start codon and eIF5-induced irreversible hydrolysis of eIF2- 26,27 However, the exact mechanism by which the mRNA threads through the narrow mRNA channel in the 40S ribosomal subunit remains a mystery. The 'open' scanningcompetent conformation of the 40S subunit allows sampling of non-AUG triplets during movement of the initiation complex, but does not lead to efficient codon-anticodon base pairing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation